1992
DOI: 10.1159/000243888
|View full text |Cite
|
Sign up to set email alerts
|

Growth Velocity of Some Fetal Parameters

Abstract: In this study, fetal growth velocities of the body weight, crown-heel length, crown-rump length and head circumference were established from 478 normal fetuses and neonates, aged 8–41 gestational weeks. The growth rates were computed by time intervals, and the velocity curves were plotted with their 95% confidence intervals. The body weight displayed an accelerating pattern of growth until 34–35 weeks and a breakdown of the growth rate afterwards, as we already observed for the brain weight in another study pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Intrauterine stunting and wasting are believed to have different timing. Length gain and weight gain peak at around 19 and 34 wk of gestation, respectively (5,21). Shortness at birth may therefore have an early onset of growth retardation, whereas a low ponderal index at birth may have a later onset in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine stunting and wasting are believed to have different timing. Length gain and weight gain peak at around 19 and 34 wk of gestation, respectively (5,21). Shortness at birth may therefore have an early onset of growth retardation, whereas a low ponderal index at birth may have a later onset in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by approximately 28 weeks, linear growth has reached 70% of term length, compared to 32% for weight (WHO, 1995) and 29% for body fat (Widdowson et al, 1979). Apart from these differences observed at birth, however, the precise timing of the peak in fetal linear growth and weight gain velocity is not known, due to the reliance on cross-sectional data on fetal size at birth (Cronk, 1983) and/or ultrasound studies of fetuses that died in the perinatal period (Guihard-Costa et al, 1991, 1992. For instance, several studies have reported different patterns of growth in cross-sectional samples compared to those based on ultrasound measurements of fetuses (Hediger et al, 1995;Goldenberg et al, 1985;Ott, 1993, Bernstein et al, 1994, 1997.…”
mentioning
confidence: 99%
“…We compared the median fetal velocity curves of our study with those of several previous studies (Fig. 3 ), including the NICHD fetal growth study [ 18 ], INTERGROWTH–21st project [ 19 ], and Guihard–Costa et al [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%